Hygiene challenges in old public housing: a case study of Rifle Range Flat, Penang - Mohd Arshard, Wan Nur Rukiah; Samsudin, Puteri Yuliana; Arminda, Wenny; Mohd Najib, Nurul ‘Ulyani (UiTM Press, 2025)
This exploratory study investigates hygiene conditions in the old public housing environment, with a focus on the Rifle Range Flats in Penang. The research aims to provide insights into the state of hygiene and the factors influencing it within this specific housing setting. Using a qualitative approach, including case study methodology and on-site observations, the study examines various aspects of hygiene, such as cleanliness, waste management, and resident perceptions. Initial findings highlight a complex interplay of factors affecting hygiene levels at the Rifle Range Flats. While residents express satisfaction with the routine rubbish collection conducted by management twice daily, concerns emerge regarding the organisation of stalls within the housing complex. Additional issues, such as pest control, ventilation, and water sanitation, are identified as critical areas for further investigation. This study's findings offer valuable implications for housing authorities and community stakeholders in developing targeted interventions to enhance hygiene standards and improve the overall wellbeing of residents in similar public housing settings.